Empirical Investigation of Job Satisfaction and Intention to Quit in the Apparel Industry of Sri Lanka - Gamage, Prasadini N.; Nuwarapaksha, Chathuranie J. S. (Gyan Management Journal, 2014)
Labor problems in garment factories have emerged as a key risk in the apparel sector. In Sri Lanka free trade zones, where most garment factories have established their manufacturing bases, are facing serious labor turnover problems. High labor turnover rates have caused poor quality, low productivity, and unfilled orders in garment factories. Turnover is the ultimate decision of the turnover intention or intention to quit of employees. This research tries to identify the root causes of job dissatisfaction leading to turnover intention and provides managerial implications that may assist managers in dealing with labor-related issues. This study was exploratory and focused on medium level garment factories in Sri Lanka. In all, 150 operational level workers selected as the sample size to respond for questionnaires on job satisfaction and intention to quit. Also there were three specific objectives; to find out the relationship between wage level of employees and intention to quit their jobs, to find out the relationship between working conditions of jobs in the apparel sector and intention to quit,finally to find out the relationship between social status/reputation they expect from their job in the apparel sector and intention to quit. Statistical results of the study revealed that there is a significant negative correlation between job satisfaction and intention to quit the jobs. Three independent variables also (wage level, working condition, social status) shows significant negative correlation with the dependant variable (intention to quit). Given the exploratory nature of this study, the results of the study have significant implications for the management of the apparel industry in Sri Lanka to prevent the issue of turnover intentions of employees which can cause to labor shortage in long term.
Keywords: Job satisfaction; Intention to Quit; Apparel Industry